Geopark development and community well-being: The case of Kinabalu UNESCO Global Geopark, Sabah, Malaysian Borneo - Oscar Dousin; Sarma Aralas; Jean Ivy Denis (Elsevier, 2024)
On May 26, 2023, the Kinabalu UNESCO Global Geopark obtained the UNESCO Global Geopark status, and it was awarded the UNESCO Triple Crown recognition, making it the third geopark globally to receive this honour. Kinabalu UNESCO Global Geopark is located in Sabah, Malaysian Borneo, and it is the nation's second geopark site. Our study aims to investigate the mediating effect of support for geopark development on the relationship between economic, sociocultural benefits, and perceived costs of geopark development on community well-being. A total of 301 participants, including those from the Kinabalu UNESCO Global Geopark's three areas of Kota Marudu, Ranau and Kota Belud, participated in the study. The findings indicate that community well-being is positively impacted by economic, sociocultural, and support for geopark development. Moreover, the support for geopark development mediates the relationship between economic and socio-cultural benefits towards community well-being. However, the study reveals that perceived costs of geopark development does not have significant effect on both relationships. Our study suggests that the local community recognizes the benefits of Kinabalu UNESCO Global Geopark in the form of income generation and opportunities for employment. However, because the geopark is still in an early stage of development, it is possible that the local community has not yet become aware of its negative aspects. The study proposes thorough and comprehensive guidelines and policies to be put in place to ensure the sustainability of the geopark regions as well as to continuously improve community well-being